PENGARUH WAKTU PENYIMPANAN TERHADAP PERTUMBUHAN CABUTAN ANAKAN ALAM MALAPOGA (Toona ciliata M. Roem) Di PERSEMAIAN - Fauzia, Fauzia; Wardah, Wardah; Irmasari, Irmasari (ForestSains, 2018)
Forest is the habitat of a wide range of plant species in which these species have different sizes and ages of seedling at transplanting. In order to increase the species richness through natural regeneration, it is important to carry out research related to this topic. In the present study, the seedlings of Malapoga (Toona ciliata M. Roem) from its natural population are investigated. It primarily aims to determine the effect of storage time of the seedlings of Malapoga (Toona ciliata M. Roem) to obtain optimal seedling growth. It was conducted in June – August 2016, at the nursery of BPDAS PALU-POSO, Universitas Tadulako, Palu, Central Sulawesi. The research uses a completely randomized design (CRD) in which there are four treatments, namely: M0 = Control, M1 = 1-day storage, M2 = 2-days storage, M3 = 3-days storage. Of the four treatments, five replications were conducted hence there were a total to 20 samples. The parameters were height, stem diameter and number of leaves. The honestly significant difference (HSD) test was carried out since the analysis of variance showed a significant difference among the treatments. The results indicate that the 3-days of storage (M3) has a significant positive effect on the seedling growth, with an average plant height of 6.94 cm, stem diameter of 0.3 mm, and eight leaves are visible. It contrasts to the control in which it experiences slow growth.